Synthesis of Two‐dimensional Microporous Carbonaceous Polymer Nanosheets and Their Application as High‐performance CO2 Capture Sorbent. Issue 12 (31st May 2016) - Zhang, Miao; Liu, Lin; He, Teng; Wu, Guotao; Chen, Ping
Abstract: The synthesis of two‐dimensional (2D) polymer nanosheets with a well‐defined microporous structure remains challenging in materials science. Here, a new kind of 2D microporous carbonaceous polymer nanosheets was synthesized through polymerization of a very low concentration of 1, 4‐dicyanobenzene in molten zinc chloride at 400–500 °C. This type of nanosheets has a thickness in the range of 3–20 nm, well‐defined microporosity, a high surface area (∼537 m 2 g −1 ), and a large micropore volume (∼0.45 cm 3 g −1 ). The microporous carbonaceous polymer nanosheets exhibit superior CO2 sorption capability (8.14 wt % at 298 K and 1 bar) and a relatively high CO2 selectivity toward N2 (25.6). Starting from different aromatic nitrile monomers, a variety of 2D carbonaceous polymer nanosheets can be obtained showing a certain universality of the ionothermal method reported herein. Abstract : A clean nanosheet : A new kind of 2D microporous carbonaceous polymer nanosheets was synthesized through polymerization of a very low concentration of 1, 4‐dicyanobenzene in molten zinc chloride at 400–500 °C. This type of nanosheets has a thickness in the range of 3–20 nm, well‐defined microporosity, a high surface area, and a large micropore volume. The microporous carbonaceous polymer nanosheets exhibit superior CO2 sorption capability and a relatively high CO2 selectivity toward N2 .